2004
DOI: 10.1101/lm.70104
|View full text |Cite
|
Sign up to set email alerts
|

Search Strategies Used byAPPTransgenic Mice During Navigation in the Morris Water Maze

Abstract: TgCRND8 mice represent a transgenic mouse model of Alzheimer's disease, with onset of cognitive impairment and increasing amyloid-␤ plaques in their brains at 12 weeks of age. In this study, the spatial memory in 25-to 30-week-old TgCRND8 mice was analyzed in two reference and one working memory Morris water maze (MWM) tests. In reference memory tests, the mice were trained to escape to a hidden platform, which in one version of the test was marked by a visual cue. In the working memory test, the hidden platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
157
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 54 publications
(44 reference statements)
16
157
0
Order By: Relevance
“…Specifically, inbred wild-type mice with excitotoxic or seizure-induced lesions of the hippocampus or entorhinal cortex are often impaired on both in the hidden-and visible-platform versions of the water maze (Hardman et al 1997;Logue et al 1997;Lipp and Wolfer 1998;Mohajeri et al 2003Mohajeri et al , 2004Lipp et al 2004). It is not clear from these studies whether hippocampal insults impair the ability to make the association between the escape platform and the discrete cue, or whether mice attempt to use a spatial strategy to solve the cued-platform version and are unable because of the lesion Hauben et al 1999;Janus 2004). Some deficits following large lesions may result from damage to association areas within the hippocampal formation .…”
mentioning
confidence: 79%
“…Specifically, inbred wild-type mice with excitotoxic or seizure-induced lesions of the hippocampus or entorhinal cortex are often impaired on both in the hidden-and visible-platform versions of the water maze (Hardman et al 1997;Logue et al 1997;Lipp and Wolfer 1998;Mohajeri et al 2003Mohajeri et al , 2004Lipp et al 2004). It is not clear from these studies whether hippocampal insults impair the ability to make the association between the escape platform and the discrete cue, or whether mice attempt to use a spatial strategy to solve the cued-platform version and are unable because of the lesion Hauben et al 1999;Janus 2004). Some deficits following large lesions may result from damage to association areas within the hippocampal formation .…”
mentioning
confidence: 79%
“…8 A, B) was not as a result of a motor disability, we examined swim speed at Ն4 months. Data from hidden platform and probe trials revealed faster swim speeds in taupositive versus tau-negative mice at 4 -7 months of age, possibly reflecting a difference in search strategy (Janus, 2004). Mean swim speeds were lower in 9.5-month-old rTg(tau P301L )4510 mice compared with controls.…”
Section: Assessment Of Motor Function In Rtg(tau P301l )4510 Micementioning
confidence: 94%
“…In other studies, some mice employ a search strategy where they circle the pool at a distance from the wall that ensures finding the platform (chaining) (Janus 2004;Patil et al 2009). With further training, Fig.…”
Section: Morris Water Mazementioning
confidence: 99%